Dilema Status Keperdataan Anak Hasil Gestational Surrogacy dalam Hukum Adat Bali: Studi Sinkronisme antara UU Kesehatan dan Asas Kapurusa : The Dilemma of the Legal Status of Children Born via Gestational Surrogacy under Balinese Customary Law: A Study of the Synchronisation between the Health Act and the Principle of Kapurusa - Ni Putu Ega Parwati; Ni Ketut Sari Adnyani; I Gusti Ayu Apsari Hadi; Ni Komang Irma Adi Sukmaningsih; Ni Luh Sukma Imagy (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This study aims to analyze the synchronicity of the civil status regulations of children resulting from gestational surrogacy (womb rental) and examine the legal standing of the child in the Kapurusa inheritance system in Bali to ensure legal certainty for Sentana. The main problem in this study is the antinomy of norms between Article 154 of Law Number 17 of 2023 concerning Health which prohibits surrogacy with the principle of Mater Semper Certa Est (the mother is the one who gives birth) in the Civil Code, which has implications for the uncertainty of the child's genetic identity. In addition, there is a dilemma in Balinese customary law where the process of birth through another woman's womb is considered to cause the status of Cemer (impure) which can revoke the child's inheritance rights as a successor to the male line (Purusa). This research is a juridical-normative legal research with a statute approach and a conceptual approach. Primary and secondary legal sources are analyzed qualitatively-normatively with a deductive thinking pattern. The research findings show that Indonesian positive law remains bogged down in the formalities of the birth process, thus severing the civil relationship between a child and its genetic mother. In Balinese customary law, children resulting from surrogacy can gain legitimacy as legitimate Sentana through a legal discovery mechanism, namely by integrating scientific evidence (DNA) into a customary village decree (Pararem) and followed by a special purification ritual (Prayascita or Pebayuh) to neutralize anomalies in the birth process. This reconstruction is crucial to protecting children's human rights and inheritance rights amidst the disruption of modern medical technology..